Design, synthesis and application of hydrogen bonded smectic liquid crystal matrix encapsulated ZnO nanospikes. Issue 45 (30th October 2015) - Pal, Kaushik; Mohan, M. L. N. Madhu; Zhan, Bihong; Wang, Guoping
Abstract : ZnO nanospikes dispersed hydrogen bonded liquid crystals, due to their novel switching properties, are promising components in a wide range of nanoscale devices for next generation applications. Abstract : ZnO nanospikes, due to their novel properties, are promising components in a wide range of nanoscale devices for future applications. Herein, current research activities are focused on the synthesis, characterization and applications of ZnO nanostructures encapsulated by a hydrogen bonded liquid crystal matrix (HBLC e.g. azelaic acid and heptyloxy benzoic acid) in optical switching. We briefly describe the smartest applied methodologies for the synthesis of ZnO nanostructures and smooth dispersion within the liquid crystalline optical materials. In fact, HBLC doping was recently found to significantly influence the nucleation and growth of many functional nanocrystals (NCs), and provide a fundamental approach to modify the crystallographic phase, size, morphology, and electronic configuration of nanomaterials. All the homologues of the present series show rich mesomorphism, exhibiting orthogonal and tilted phases. A range of remarkable characteristics is then presented, organized into sections describing the optical, electrical and electro-optical phase transitions and DC bi-stable switching properties. The other display parameters such as spontaneous polarization, rotational viscosity, switching response, capacitance, dielectric permittivity, dielectric loss spectra and low frequency relaxation (Goldstone mode) are also investigated for these nanospike–HBLC composites, and support the observations described in this article. Moreover, polarizing optical microscopy reveals various phases with different textural appearances, which proves the influence of the nanomaterial. Most observed phenomena are discussed in terms of a new smectic ordering, named smectic X*, which is sandwiched between traditional nematic and convectional smectic C* phases. Dielectric relaxations in the smectic C* phases of pure and doped LCs have been analyzed. In this feature article, we provide an overview of the most recent progresses in HBLC (AC + 7BAO) doping-induced control of efficient switching, as well as the high performances of novel functional nanomaterials, for the first time. These investigations are developing versatile applications of opto-electronic and high resolution liquid crystal devices.